The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Educating for psychological, community, and ecological resilience: a case study from North Carolina, USA - Aurora R. McCollum; Kathryn T. Stevenson; Kelsey Tayne; Elizabeth DeMattia; Patrick Jeffs; K. C. Busch (Journal of Environmental Studies and Sciences, 2026)

Tolerance to future elevated CO2 conditions in sablefish (Anoplopoma fimbria), a deep-water benthic dwelling fish species - Chase R. Williams; Evan P. Gallagher; Paul McElhany; D. Shallin Busch; Michael T. Maher; Andrew H. Dittman (Journal of Comparative Physiology A, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Management practices and soil health: Insights from dairy farms in the United States - Che-Jen Hsiao; Mara Cloutier; Daniel Liptzin; Nathaniel Looker; Christine Molling; Michael Cope; Randall D. Jackson; Gregg R. Sanford; Matthew D. Ruark; Dennis Busch; Karl Czymmek; Quirine M. Ketterings; et al. (Agriculture, Ecosystems & Environment, 2026)

Does an arctic circumpolar distribution exist for deep-sea sponges? Unravelling the systematics of Stylocordyla borealis (Porifera: Demospongiae) through integrative taxonomy - Franziska I. Theising; Ute Hentschel; Kathrin Busch; Angelika Brandt; Francisca Carvalho; Joana R. Xavier; Andreu Santín Muriel (Progress in Oceanography, 2026)

Population genetic structure in two contrasting human-altered environments of yellow pygmy rice rat Oligoryzomys flavescens - E. Muschetto; I. E. Gómez Villafañe; M. Scaltritti; J. Fraschina; V. León; L. Adduci; D. Hancke; S. Guidobono; G. R. Cueto; M. A. Tripodi; E. Hasson; M. Busch; et al. (Oecologia, 2025)

Semi-structured citizen science data reveal mixed effectiveness of EU Special Protection Areas (SPA) in Germany - F.J. Pflüger; C. Frank; M. Busch; J. Wahl; R. Dröschmeister; C. Sudfeldt; J. Kamp (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Global patterns of allochthony in stream–riparian meta‐ecosystems - Daniel C. Allen; James Larson; Christina A. Murphy; Erica A. Garcia; Kurt E. Anderson; Michelle H. Busch; Alba Argerich; Alice M. Belskis; Kierstyn T. Higgins; Brooke E. Penaluna; Veronica Saenz; Jay Jones; et al. (Ecology Letters, 2024)
Ecosystems that are coupled by reciprocal flows of energy and nutrient subsidies can be viewed as a single “meta‐ecosystem.” Despite these connections, the reciprocal flow of subsidies is greatly asymmetrical and seasonally pulsed. Here, we synthesize existing literature on stream–riparian meta‐ecosystems to quantify global patterns of the amount of subsidy consumption by organisms, known as “allochthony.” These resource flows are important since they can comprise a large portion of consumer diets, but can be disrupted by human modification of streams and riparian zones. Despite asymmetrical subsidy flows, we found stream and riparian consumer allochthony to be equivalent. Although both fish and stream invertebrates rely on seasonally pulsed allochthonous resources, we find allochthony varies seasonally only for fish, being nearly three times greater during the summer and fall than during the winter and spring. We also find that consumer allochthony varies with feeding traits for aquatic invertebrates, fish, and terrestrial arthropods, but not for terrestrial vertebrates. Finally, we find that allochthony varies by climate for aquatic invertebrates, being nearly twice as great in arid climates than in tropical climates, but not for fish. These findings are critical to understanding the consequences of global change, as ecosystem connections are being increasingly disrupted.

Analysis of vascular disruption in zebrafish embryos as an endpoint to predict developmental toxicity - Julia Nöth; Wibke Busch; Tamara Tal; Chih Lai; Akhil Ambekar; Tobias R. Kießling; Stefan Scholz (Archives of Toxicology, 2024)
Inhibition of angiogenesis is an important mode of action for the teratogenic effect of chemicals and drugs. There is a gap in the availability of simple, experimental screening models for the detection of angiogenesis inhibition. The zebrafish embryo represents an alternative test system which offers the complexity of developmental differentiation of an entire organism while allowing for small-scale and high-throughput screening. Here we present a novel automated imaging-based method to detect the inhibition of angiogenesis in early life stage zebrafish. Video subtraction was used to identify the location and number of functional intersegmental vessels according to the detection of moving blood cells. By exposing embryos to multiple tyrosine kinase inhibitors including SU4312, SU5416, Sorafenib, or PTK787, we confirmed that this method can detect concentration-dependent inhibition of angiogenesis. Parallel assessment of arterial and venal aorta ruled out a potential bias by impaired heart or blood cell development. In contrast, the histone deacetylase inhibitor valproic acid did not affect ISV formation supporting the specificity of the angiogenic effects. The new test method showed higher sensitivity, i.e. lower effect concentrations, relative to a fluorescent reporter gene strain (Tg(KDR:EGFP)) exposed to the same tyrosine kinase inhibitors indicating that functional effects due to altered tubulogenesis or blood transport can be detected before structural changes of the endothelium are visible by fluorescence imaging. Comparison of exposure windows indicated higher specificity for angiogenesis when exposure started at later embryonic stages (24 h post-fertilization). One of the test compounds was showing particularly high specificity for angiogenesis effects (SU4312) and was, therefore, suggested as a model compound for the identification of molecular markers of angiogenic disruption. Our findings establish video imaging in wild-type strains as viable, non-invasive, high-throughput method for the detection of chemical-induced angiogenic disruption in zebrafish embryos.

Correction to: Picking up speed: cell cycle regulation during effector CD8+ T cell differentiation - Lorenz Kretschmer; Noémie Fuchs; Dirk H. Busch; Veit R. Buchholz (Medical Microbiology and Immunology, 2023)

Picking up speed: cell cycle regulation during effector CD8+ T cell differentiation - Lorenz Kretschmer; Noémie Fuchs; Dirk H. Busch; Veit R. Buchholz (Medical Microbiology and Immunology, 2023)
Clonal expansion and development of immunological memory are two hallmarks of adaptive immune responses. Resolving the intricate pathways that regulate cell cycle activity and lead to the generation of diverse effector and memory T cell subsets is essential for improving our understanding of protective T cell immunity. A deeper knowledge of cell cycle regulation in T cells also has translational implications for adoptive cell therapies and vaccinations against infectious diseases. Here, we summarize recent evidence for an early diversification of effector and memory CD8 + T cell fates and discuss how this process is coupled to discrete changes in division speed. We further review technical advances in lineage tracing and cell cycle analysis and outline how these techniques have shed new light on the population dynamics of CD8 + T cell responses, thereby refining our current understanding of the developmental organization of the memory T cell pool.

Evaluating environmental controls on the exoskeleton density of larval Dungeness crab via micro computed tomography - Casey P. Saenger; Paul McElhany; Emily L. Norton; D. Shallin Busch; Samantha A. Siedlecki; Simone R. Alin; Richard A. Feely; Albert J. Hermann; Nina Bednaršek (Frontiers in Marine Science, 2023)
Dungeness crab ( Metacarcinus magister ) have significant socioeconomic value, but are threatened by ocean acidification (OA) and other environmental stressors that are driven by climate change. Despite evidence that adult harvests are sensitive to the abundance of larval populations, relatively little is known about how Dungeness megalopae will respond to these stressors. Here we evaluate the ability to use micro-computed tomography (μCT) to detect variations in megalope exoskeleton density and how these measurements reflect environmental variables and calcification mechanisms. We use a combination of field data, culture experiments, and model simulations to suggest resolvable differences in density are best explained by minimum pH at the time zoeae molt into megalopae. We suggest that this occurs because more energy must be expended on active ion pumping to reach a given degree of calcite supersaturation at lower pH. Energy availability may also be reduced due to its diversion to other coping mechanisms. Alternate models based on minimum temperature at the time of the zoea-megalope molt are nearly as strong and complicate the ability to conclusively disentangle pH and temperature influences. Despite this, our results suggest that carryover effects between life stages and short-lived extreme events may be particularly important controls on exoskeleton integrity. μCT-based estimates of exoskeleton density are a promising tool for evaluating the health of Dungeness crab populations that will likely provide more nuanced information than presence-absence observations, but future in situ field sampling and culture experiments are needed to refine and validate our results.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Lower Vibrio spp. abundances in Zostera marina leaf canopies suggest a novel ecosystem function for temperate seagrass beds - Thorsten B. H. Reusch; Philipp R. Schubert; Silke-Mareike Marten; Diana Gill; Rolf Karez; Kathrin Busch; Ute Hentschel (Marine Biology, 2021)
Seagrasses, a polyphyletic group of about 60 marine angiosperm species, are the foundation of diverse and functionally important marine habitats along sheltered sedimentary coasts. As a novel ecological function with high societal relevance, a role of the seagrass leaf canopy for reducing potentially harmful bacteria has recently been hypothesized in tropical regions, but data for temperate regions are lacking. Here, we tested whether or not the abundance of general bacteria and more specifically, those belonging to the genus Vibrio were reduced within temperate Zostera marina (eelgrass) meadows compared to adjacent sand flats and sampled 5 sites in the south-western Baltic Sea using SCUBA. Compared to non-vegetated area, we found an average reduction of 39% for all Vibrio and 63% for the potentially harmful V. vulnificus/cholerae subtype based on robust plate counting data on Vibrio selective agar. The underlying mechanism of the reduction in bacterial load is currently elusive and clearly merits further study. Our results underline the critical importance of seagrasses in maintaining shallow water ecosystem functioning including water quality and provide further motivation for their protection and restoration.

Reducing Data Deficiencies: Preliminary Elasmobranch Fisheries Surveys in India, Identify Range Extensions and Large Proportions of Female and Juvenile Landings - Shaili Johri; Isabella Livingston; Anjani Tiwari; Jitesh Solanki; Anissa Busch; Isabel Moreno; Sam R. Fellows; Michael P. Doane; Elizabeth A. Dinsdale (Frontiers in Marine Science, 2021)
Chondrichthyes, an ancient and diverse class of vertebrates, are crucial to the health of marine ecosystems. Excessive demand for chondrichthyan products has increased fishing pressure, threatening ∼30% of species with extinction in recent decades. India is the second-largest shark landing nation globally and the province of Gujarat, is the largest contributor to its shark exports. Despite their significant contribution to global fish supplies, chondrichthyan fisheries in Gujarat remain understudied and many species, data deficient, posing challenges to the conservation of remaining populations in the region. Here, we report results from taxonomic assessment of elasmobranchs at four key landing sites in Gujarat. We identified thirty-one species of sharks and rays with a significant bias toward capture of females and juveniles by fisheries. Our data indicate the presence of nursery areas for species such as Sphyrna lewini and Rhynchobatus laevis in the neritic areas off Gujarat. Further, we discovered extensions of the current distribution range for three species - Torpedo sinuspersici , Carcharhinus sorrah , and Rhinobatos punctifer . Taxonomic identities for a subset of species were confirmed using genomic analyses conducted with portable DNA sequencing tools. We present assessments for six data deficient species in the region – Rhinobatos annandalei , Rhinoptera jayakari , Maculabatis bineeshi, Pateobatis bleekeri, T. sinuspersici , and Carcharhinus amboinensis. Our investigation underscores species with urgent conservation needs and reduces data deficiencies. These data will inform and pivot future scientific and conservation efforts to protect remaining populations of some of the most vulnerable Chondrichthyes in the Arabian Seas Region.

Diversity and distribution of the bmp gene cluster and its Polybrominated products in the genus Pseudoalteromonas - Julia Busch; Vinayak Agarwal; Michelle Schorn; Henrique Machado; Bradley S. Moore; Greg W. Rouse; Lone Gram; Paul R. Jensen (Environmental Microbiology, 2019)
Summary The production of pentabromopseudilin and related brominated compounds by Pseudoalteromonas spp. has recently been linked to the bmp biosynthetic gene cluster. This study explored the distribution and evolutionary history of this gene cluster in the genus Pseudoalteromonas . A phylogeny of the genus revealed numerous clades that do not contain type strains, suggesting considerable species level diversity has yet to be described. Comparative genomics revealed four distinct versions of the gene cluster distributed among 19 of the 101 Pseudoalteromonas genomes examined. These were largely localized to the least inclusive clades containing the Pseudoalteromonas luteoviolacea and Pseudoalteromonas phenolica type strains and show clear evidence of gene and gene cluster loss in certain lineages. Bmp gene phylogeny is largely congruent with the Pseudoalteromonas species phylogeny, suggesting vertical inheritance within the genus. However, the gene cluster is found in three different genomic environments suggesting either chromosomal rearrangement or multiple acquisition events. Bmp conservation within certain lineages suggests the encoded products are highly relevant to the ecology of these bacteria.

Elevated CO 2 impairs olfactory‐mediated neural and behavioral responses and gene expression in ocean‐phase coho salmon ( Oncorhynchus kisutch ) - Chase R. Williams; Andrew H. Dittman; Paul McElhany; D. Shallin Busch; Michael T. Maher; Theo K. Bammler; James W. MacDonald; Evan P. Gallagher (Global Change Biology, 2019)
Elevated concentrations of CO 2 in seawater can disrupt numerous sensory systems in marine fish. This is of particular concern for Pacific salmon because they rely on olfaction during all aspects of their life including during their homing migrations from the ocean back to their natal streams. We investigated the effects of elevated seawater CO 2 on coho salmon ( Oncorhynchus kisutch ) olfactory‐mediated behavior, neural signaling, and gene expression within the peripheral and central olfactory system. Ocean‐phase coho salmon were exposed to three levels of CO 2 , ranging from those currently found in ambient marine water to projected future levels. Juvenile coho salmon exposed to elevated CO 2 levels for 2 weeks no longer avoided a skin extract odor that elicited avoidance responses in coho salmon maintained in ambient CO 2 seawater. Exposure to these elevated CO 2 levels did not alter odor signaling in the olfactory epithelium, but did induce significant changes in signaling within the olfactory bulb. RNA‐Seq analysis of olfactory tissues revealed extensive disruption in expression of genes involved in neuronal signaling within the olfactory bulb of salmon exposed to elevated CO 2 , with lesser impacts on gene expression in the olfactory rosettes. The disruption in olfactory bulb gene pathways included genes associated with GABA signaling and maintenance of ion balance within bulbar neurons. Our results indicate that ocean‐phase coho salmon exposed to elevated CO 2 can experience significant behavioral impairments likely driven by alteration in higher‐order neural signal processing within the olfactory bulb. Our study demonstrates that anadromous fish such as salmon may share a sensitivity to rising CO 2 levels with obligate marine species suggesting a more wide‐scale ecological impact of ocean acidification.

The accessory magnocellular neurosecretory system of the rostral human hypothalamus - Morten Møller; Johannes R. Busch; Christina Jacobsen; Sissel B. Lundemose; Niels Lynnerup; Martin F. Rath; Jytte Banner (Cell and Tissue Research, 2018)

Atlantic salmon, S almo salar L . are broadly susceptible to isolates representing the N orth A merican genogroups of infectious hematopoietic necrosis virus - G Kurath; J R Winton; O B Dale; M K Purcell; K Falk; R A Busch (Journal of Fish Diseases, 2016)
Beginning in 1992, three epidemic waves of infectious hematopoietic necrosis, often with high mortality, occurred in farmed A tlantic salmon S almo salar L . on the west coast of N orth A merica. We compared the virulence of eleven strains of infectious hematopoietic necrosis virus ( IHNV ), representing the U , M and L genogroups, in experimental challenges of juvenile A tlantic salmon in freshwater. All strains caused mortality and there was wide variation within genogroups: cumulative mortality for five U ‐group strains ranged from 20 to 100%, four M ‐group strains ranged 30‐63% and two L ‐group strains varied from 41 to 81%. Thus, unlike P acific salmonids, there was no apparent correlation of virulence in a particular host species with virus genogroup. The mortality patterns indicated two different phenotypes in terms of kinetics of disease progression and final per cent mortality, with nine strains having moderate virulence and two strains (from the U and L genogroups) having high virulence. These phenotypes were investigated by histopathology and immunohistochemistry to describe the variation in the course of IHNV disease in A tlantic salmon. The results from this study demonstrate that IHNV may become a major threat to farmed A tlantic salmon in other regions of the world where the virus has been, or may be, introduced.

Opportunities and Challenges in the Design and Analysis of Biomass Supply Chains - Pasi T. Lautala; Michael R. Hilliard; Erin Webb; Ingrid Busch; J. Richard Hess; Mohammad S. Roni; Jorge Hilbert; Robert M. Handler; Roger Bittencourt; Amir Valente; Tuuli Laitinen (Environmental Management, 2015)

Implications of p75NTR for dentate gyrus morphology and hippocampus-related behavior revisited - M. Dokter; R. Busch; R. Poser; M. A. Vogt; V. von Bohlen und Halbach; P. Gass; K. Unsicker; O. von Bohlen und Halbach (Brain Structure and Function, 2015)

Erratum to: Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Method Transfer, Partial Validation, and Cross Validation: Recommendations for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - R. J. Briggs; R. Nicholson; F. Vazvaei; J. Busch; M. Mabuchi; K. S. Mahesh; M. Brudny-Kloeppel; N. Weng; P. A. R. Galvinas; P. Duchene; Pei Hu; R. W. Abbott (The AAPS Journal, 2014)

Demographic and population‐genetic tests provide mixed support for the abundant centre hypothesis in the endemic plant Leavenworthia stylosa - Andrea L. Dixon; Christopher R. Herlihy; Jeremiah W. Busch (Molecular Ecology, 2013)
The abundant centre hypothesis ( ACH ) assumes that population abundance, population size, density and per‐capita reproductive output should peak at the centre of a species' geographic range and decline towards the periphery. Increased isolation among and decreased reproductive output within edge populations should reduce within‐population genetic diversity and increase genetic differentiation among edge relative to central populations. The ACH also predicts asymmetrical gene flow, with net movement of migrants from the centre to edges. We evaluated these ecological assumptions and population‐genetic predictions in the endemic flowering plant Leavenworthia stylosa . Although populations were more spatially isolated near range edges, the geographic centre was surrounded by and not coincident with areas of peak population abundance, and plant density increased towards range edges. Per‐capita seed number was not associated with distance to the range centre, but seed number/m 2 increased near range edges. In support of ACH predictions, allelic diversity at 12 microsatellite loci declined with distance from the range centre, and pairwise F ST values were higher between edge populations than between central populations. Coalescent analyses confirmed that gene flow was most infrequent between edge populations, but there was not an asymmetric pattern of gene flow predicted by the ACH . This study shows that among‐population demographic variability largely did not support the ACH , while patterns of genetic diversity, differentiation and gene flow were generally consistent with its predictions. Such mixed support has frequently been observed in tests of the ACH and raises concerns regarding the generality of this hypothesis for species range limits.

Narrow species concepts in the Frullania dilatata–appalachiana–eboracensis complex (Porellales, Jungermanniopsida): evidence from nuclear and chloroplast DNA markers - A. Bombosch; A. Wieneke; A. Busch; R. Jonas; J. Hentschel; H.-P. Kreier; B. Shaw; A. J. Shaw; J. Heinrichs (Plant Systematics and Evolution, 2010)

Nachweis von Clostridium botulinum Typ A, B, E und F mittels real-time-PCR - U. Messelhäusser; R. Zucker; H. Ziegler; D. Elmer-Englhard; W. Kleih; C. Höller; U. Busch (Journal of Consumer Protection and Food Safety, 2007)

“Technically Unavoidable” in Terms of Genetically Modified Organisms – an Approach for Food Control - H.-U. Waiblinger; N. Graf; D. Mäde; K. Woll; U. Busch; B. Holland; H. Pilsl; G. Naeumann; R. Reiting; B. Ehrentreich; M. Schulze; B. Tschirdewahn; et al. (Journal of Consumer Protection and Food Safety, 2007)

Nachweis und Charakterisierung von Clostridium perfringens mittels real-time-PCR - U. Messelhäusser; R. Zucker; D. Elmer-Englhard; U. Busch; S. Hörmansdorfer; U. Pudich; C. Höller (Journal of Consumer Protection and Food Safety, 2007)

Parentage analysis detects cryptic precapture dispersal in a philopatric rodent - PETER M. WASER; JOSEPH D. BUSCH; CORY R. McCORMICK; J. ANDREW DEWOODY (Molecular Ecology, 2006)
Locating birthplaces using genetic parentage determination can increase the precision and accuracy with which animal dispersal patterns are established. We re‐analyse patterns of movement away from the birthplace as a function of time, sex and population density for a sample of 303 banner‐tailed kangaroo rats, Dipodomys spectabilis. We located birth sites using a combination of likelihood‐based parentage analysis with live‐trapping of mothers during the breeding season. The results demonstrate that natal‐breeding site distances are density dependent in this species; in particular, both sexes emigrate earlier in the year, and females disperse farther than males, at low population densities. Banner‐tailed kangaroo rats were chosen as a study system because live‐trapping easily detects maternal and offspring locations; nevertheless, parentage analysis reveals that some offspring evade early detection and move substantial distances before their first capture. In a few cases, the approach even detects dispersal out of the natal ‘deme’ prior to first capture. Parentage analysis confirms the extreme philopatry of both sexes but indicates that prior estimates of median dispersal distance were too low. For D. spectabilis , more accurate location of individual birthplaces clarifies patterns of sex bias and density dependence in dispersal, and may resolve apparent discrepancies between direct and indirect estimates of dispersal distance. For species in which mothers can be more reliably trapped than juveniles, using offspring genotypes to locate parents is a novel way that genetic techniques can contribute to the analysis of animal dispersal.

Use of Chemical Communication by the Subterranean Rodent Ctenomys talarum (Tuco-Tuco) During the Breeding Season - Roxana R. Zenuto; Maria S. Fanjul; Cristina Busch (Journal of Chemical Ecology, 2004)

Epidemiology of rubella infections in Austria: important lessons to be learned - B. Falkensammer; G. Walder; D. Busch; A. Gieauf; M. Dierich; R. Wrzner (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Infilling of the Younger Kathmandu–Banepa intermontane lake basin during the Late Quaternary (Lesser Himalaya, Nepal): a sedimentological study - H. G. Dill; D. R. Khadka; R. Khanal; R. Dohrmann; F. Melcher; K. Busch (Journal of Quaternary Science, 2003)
The Kathmandu and Banepa Basins, Central Nepal, are located in a large syncline of the Lesser Himalayas. The Older Kathmandu Lake evolved during the Pliocene and early Pleistocene; the Younger Kathmandu Lake, which is the focus of this study, is infilled with late Quaternary sediments. Three formations, arranged in stratigraphical order, the Kalimati, Gokarna and Thoka Formations formed during the infilling stage of this lacustrine basin. Structural and textural sedimentological analyses, a chemical survey across the basin and mineralogical investigations of fine‐grained sediments form the basis of this palaeogeographical study. The basin under investigation was covered by a perennial freshwater lake before 30 000 yr BP. The lake was infilled with alluvial and fluvial sediments delivered mainly from the mountains north of the basin. A fairly low gradient was favourable for the formation of diatomaceous earths, carbonaceous mudstones and siltstones, which were laid down in the centre of the lake and in small ponds. Towards the basin edge, lacustrine sediments gave way to deltaic deposits spread across the delta plain. Crevasse splays and anastomosing rivers mainly delivered suspended load for the widespread siltstones and mudstones. The proximal parts of the alluvial–fluvial sedimentary wedge contain debris flows that interfinger with fine‐grained floodplain deposits. Three highstands of the water‐level (>30 000 yr BP, 28 000–19 000 yr BP, 11 000–4000 yr BP (?)) have been recognised in the sedimentary record of the younger Kathmandu Lake in the Late Quaternary. Second‐order water‐level fluctuations are assumed to be triggered by local processes (damming by tectonically induced landslides). First‐order water‐level fluctuations are the result of climatic changes. Copyright © 2003 John Wiley & Sons, Ltd.

Influence of weather and climate on subjective symptom intensity in atopic eczema - E. Vocks; R. Busch; C. Fröhlich; S. Borelli; H. Mayer; J. Ring (International Journal of Biometeorology, 2001)

Characterisation of oxidised 7Fe dicluster ferredoxins with NMR spectroscopy - Jonathan P. Hannan; Johanneke L. H. Busch; Jacques Breton; Richard James; Andrew J. Thomson; Geoffrey R. Moore; S. L. Davy (JBIC Journal of Biological Inorganic Chemistry, 2000)

Effect of urea and osmotic cell shrinkage on Ca2+ entry and contraction of vascular smooth muscle cells - C.A. Wagner; S.M. Huber; S. Wärntges; G. Zempel; N.K. Kaba; R. Fux; N. Orth; G.L. Busch; S. Waldegger; I. Lambert; B. Nilius; H. Heinle; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

Degradation of desferrioxamines by Azospirillum irakense: Assignment of metabolites by HPLC/electrospray mass spectrometry - G. Winkelmann; B. Busch; A. Hartmann; G. Kirchhof; R. Süßmuth; G. Jung (BioMetals, 1999)

DNA fingerprinting reveals polygyny in the subterranean rodent Ctenomys talarum - Roxana R. Zenuto; Eileen A. Lacey; Cristina Busch (Molecular Ecology, 1999)
DNA fingerprinting was used to characterize patterns of paternity in two populations of Ctenomys talarum from Buenos Aires Province, Argentina. The multilocus probe PV47–2 was used to detect variation in genomic DNA extracted from 12 females, their 32 offspring, and 14 putative sires. For 11 out of 12 litters examined, a single male capable of providing all nonmaternal bands was identified. Within each study population, individual males sired more than one litter, suggesting that C. talarum is polygynous. No evidence of multiple paternity of litters was found. High band‐sharing values among females suggest that further research is needed to assess the population genetic structure of this species.

Agronomic performance of lines derived from anther culture, maize pollination and single-seed descent in a spring wheat cross - H. Ma; R. H. Busch; O. Riera-Lizarazu; H. W. Rines; R. Dill-Macky (Theoretical and Applied Genetics, 1999)

Water relations of riparian plants from warm desert regions - Stanley D. Smith; Dale A. Devitt; Anna Sala; James R. Cleverly; David E. Busch (Wetlands, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Depression After Mild Traumatic Brain Injury: A Review of Current Research - Chardelle R. Busch; Herbert P. Alpern (Neuropsychology Review, 1998)

Structural rearrangement in chromosome 2M of Aegilops comosa has prevented the utilization of the Compair and related wheat-Ae. comosa translocations in wheat improvement - S. Nasuda; B. Friebe; W. Busch; R. G. Kynast; B. S. Gill (Theoretical and Applied Genetics, 1998)

Rapid isolation of muscle and heart mitochondria, the lability of oxidative phosphorylation and attempts to stabilize the process in vitro by taurine, carnitine and other compounds - Hans R. Scholte; Yihong Yu; John D Ross; Imma I. Oosterkamp; Adriana M.C. Boonman; Herman F.M. Busch (Molecular and Cellular Biochemistry, 1997)

K V LQT channels are inhibited by the K + channel blocker 293B - M. Bleich; M. Briel; A. E. Busch; H. J. Lang; U. Gerlach; H. Gögelein; R. Greger; K. Kunzelmann (Pflügers Archiv - European Journal of Physiology, 1997)

Potato seed-piece treatment in Ontario - L. V. Busch; R. G. Rowberry (American Journal of Potato Research, 1972)